2017
DOI: 10.1158/1055-9965.epi-16-0796
|View full text |Cite
|
Sign up to set email alerts
|

Body Size Indicators and Risk of Gallbladder Cancer: Pooled Analysis of Individual-Level Data from 19 Prospective Cohort Studies

Abstract: Background There are few established risk factors for gallbladder cancer beyond gallstones. Recent studies suggest a higher risk with high body mass index (BMI), an indicator of general heaviness, but evidence from other body size measures is lacking. Methods Associations of adult BMI, young adult BMI, height, adult weight gain, waist circumference (WC), waist-height ratio (WHtR), hip circumference (HC), and waist-hip ratio (WHR) with gallbladder cancer risk were evaluated. Individual-level data from 1,878,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…In addition, we saw no evidence that the risk of any of the BTCs differed by sex, though other studies have (38,39). Our study was largely comprised of postmenopausal women and is consistent with previous research that shows the sex disparity for BTCs narrows in older ages (14,21,40).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, we saw no evidence that the risk of any of the BTCs differed by sex, though other studies have (38,39). Our study was largely comprised of postmenopausal women and is consistent with previous research that shows the sex disparity for BTCs narrows in older ages (14,21,40).…”
Section: Discussionsupporting
confidence: 89%
“…Our study expands on previously pooled analyses, which also found that adiposity was associated with GBC and IHBDC risk (14,21,33). Most research on adiposity has focused on BMI and do not always included measures abdominal obesity, such as waist circumference, hip circumference, waist-to-hip ratio, and waist-to-height ratio.…”
Section: Discussionmentioning
confidence: 50%
“…26 Obesity rates in Latin America have increased, 27 and obesity has been established as a risk factor for not only pancreatic malignancies but also for gallbladder malignancies. 13,28 The obesity factor may have contributed to the highest incidence and mortality rates of gallbladder cancer observed in Southern Latin America and Andean Latin America. 29 Chile, Uruguay, and Argentina (Southern Latin America) saw the largest decrease in incidence and mortality from biliary and gallbladder cancers, perhaps because of the implementation of health policies on prevention and early disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…The only significant association was with gallbladder cancer, and notably, with mucinous ovarian cancers in the two-way comparison. Some common risk factors, such as smoking and obesity, may contribute to the association between ovarian cancer and gallbladder cancer 3 , 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%